1996
DOI: 10.1001/archinte.1996.00440160119014
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure

Abstract: Bilateral upper-extremity blood pressure determinations, as measured by automated indirect measurement, have a wide degree of interarm variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…This difference can be attributable to random variation but it also could indicate that those subjects suffered from a cardiac disease, e.g. coarcation of the aorta, upper extremity arterial obstruction, dissection or aneurysm of the thoracic aorta [10, 12, 19, 26], and thus the inter-arm difference could mask treatment effects. Unfortunately, this hypothesis cannot be tested, as this accurate diagnostic information is not available for the study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference can be attributable to random variation but it also could indicate that those subjects suffered from a cardiac disease, e.g. coarcation of the aorta, upper extremity arterial obstruction, dissection or aneurysm of the thoracic aorta [10, 12, 19, 26], and thus the inter-arm difference could mask treatment effects. Unfortunately, this hypothesis cannot be tested, as this accurate diagnostic information is not available for the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have suggested a bias towards higher readings from the right arm [911], whereas others have failed to show this [1215]. Additionally, disagreement exists as to whether body position would make any difference in BP readings [6, 1618].…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion criteria included patients with a MAP difference of more than 20 mmHg between their upper arms as measured by automated oscillometric NIBP, a history of or concurrent known arterial vascular occlusive diseases such as thromboangiitis obliterans, Takayasu's disease, Raynaud's disease, lupus, scleroderma, rheumatoid arthritis, thoracic outlet syndrome, and a history of upper extremity embolisation. 20,21 Contraindications for intra-arterial catheterisation including a negative Allen test, a history of Raynaud's phenomenon or brachial artery injury, which were also not considered for enrolment. 21 Patients with contraindications to non-invasive blood pressure cuff placement such as the presence of an upper limb arteriovenous fistula for renal dialysis, previous lymph node removal and lymphoedema were also not considered for enrolment.…”
Section: Methodsmentioning
confidence: 99%
“…Typical presentation for aortic dissection is the sudden onset of severe chest pain radiating to the back and frequently associated with sweating [Chen et al 1997;Klompas 2002;Januzzi et al 2004;Creager and Loscalzo 2015;AHA 2016]. Nonspecific signs during physical examination are differences among carotid, radial, and femoral pulses [Klompas 2002]; differences in blood pressure between the two arms [Singer and Hollander 1996;Von Kodolitsch et al 2000]; and a heart murmur heard through a…”
Section: Aortic Dissectionmentioning
confidence: 99%